LITHISTID SPONGES DERIVED COMPOUNDS AND THEIR IMPORTANCE IN BIOLOGICAL RESEARCH - A REVIEW - M, Abirla; Devi P, Brindha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Lithistid sponges have an important source of complex natural compounds with biological activities. The lithistid sponges are of interest to biomedical science because of the great variety of pharmaceutically relevant biological activities of their chemical extracts and are considered as economically important. The compounds identified in these sponges have therapeutic potential and have been frequently hypothesized to contain compounds of bacterial origin. The peptides identified from these lithistid sponges are found to be the sources of antifungal activity. The active agents of these sponges also have cytotoxic and immunosuppressive activities. Many of the cyclic peptides of lithistid represent the anti-HIV activity. The different structure and biological activities of the compounds derived from these sponges have more chemical aspects too.